Respuestas
Respuesta dada por:
2
Hola!
Es muy simple, se debe resolver usando proporciones
![\dfrac{cateto_A \ opuesto}{cateto_A \ adyacente} = \dfrac{cateto_B\ opuesto}{cateto_B\ adyacente} \\ \\ \\ \dfrac{3\ m}{1,5\ m} = \dfrac{x}{4\ m} \\ \\ \\ 3\ m*4\ m= x*1,5\ m \\ \\ \dfrac{12\ m^2}{1,5\ m}= x\qquad\to\qquad \boxed{x= 8\ m} \dfrac{cateto_A \ opuesto}{cateto_A \ adyacente} = \dfrac{cateto_B\ opuesto}{cateto_B\ adyacente} \\ \\ \\ \dfrac{3\ m}{1,5\ m} = \dfrac{x}{4\ m} \\ \\ \\ 3\ m*4\ m= x*1,5\ m \\ \\ \dfrac{12\ m^2}{1,5\ m}= x\qquad\to\qquad \boxed{x= 8\ m}](https://tex.z-dn.net/?f=+%5Cdfrac%7Bcateto_A+%5C+opuesto%7D%7Bcateto_A+%5C+adyacente%7D+%3D++%5Cdfrac%7Bcateto_B%5C+opuesto%7D%7Bcateto_B%5C+adyacente%7D+%5C%5C++%5C%5C++%5C%5C+++%5Cdfrac%7B3%5C+m%7D%7B1%2C5%5C+m%7D+%3D++%5Cdfrac%7Bx%7D%7B4%5C+m%7D+%5C%5C++%5C%5C++%5C%5C++3%5C+m%2A4%5C+m%3D+x%2A1%2C5%5C+m+%5C%5C++%5C%5C++%5Cdfrac%7B12%5C+m%5E2%7D%7B1%2C5%5C+m%7D%3D++x%5Cqquad%5Cto%5Cqquad++%5Cboxed%7Bx%3D+8%5C+m%7D+)
Espero que te sirva, salu2!!!!
Es muy simple, se debe resolver usando proporciones
Espero que te sirva, salu2!!!!
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años